EIA decision-making and administrative justice: the substance of just decisions. Issue 4 (4th July 2022) - Alberts, R.C.; Retief, F.P.; Arts, J.; Roos, C.; Cilliers, D.P; Fischer, T.B.
ABSTRACT: In this paper we aim at determining the link between EIA report substance and administratively just EIA decisions. In so doing, previous research based on 42 case studies from South Africa, which analysed whether they comprised administratively just decisions (i.e. that were lawful, procedurally fair and reasonable) were reviewed for the substance of the EIA reports on which the decisions were based. The research found that administratively just decisions can be achieved even with weak EIA report substance in areas such as: need and desirability, identifying alternatives, dealing with significance, and addressing mitigation measures. We thereby conclude that administrative justice may be a false safety net in ensuring more environmentally sustainable EIA outcomes if not supported and informed by good EIA report substance. We conclude by making recommendations to improve substance and thereby strengthening administrative justice in EIA.